Unveiling the Enigmatic Dwarf Horseface Loach Acanthopsoides molobrion: A Groundbreaking Discovery in Indonesia (Biosaintifika: Journal of Biology & Biology Education, 2024)
Acanthopsoides molobrion is a freshwater previously known to be spread across Malaysia and Borneo. This study aimed to record for the first time the occurrence of the A. molobrion in Bangka Island, Indonesia, and update the geographic distribution of this species. This new record of freshwater fish provides an important contribution to the comprehension of the biogeography of the species. The purpose sampling approach was employed for this study to collect specimens. The species were then identified morphologically by the application of morphometric and meristic methods, and molecularly through the employ of DNA Barcoding. On 20th January 2023, two A. molobrion specimens were collected from the Bumang Kemuja River, Bangka Island using a fish trap. The new record of A. molobrion found here is the southernmost record for this species, expanding its geographic distribution. In addition, the latest record site is about 500 km south of the nearest locality in Peninsular Malaysia, and about 750 km southwest of the nearest locality in Borneo. The new record of A. molobrion has expanded the species' recorded distribution range, which has added to our understanding of this species. Furthermore, we present an updated record for the A. molobrion DNA sequence based on the COI gene. This sequence is the first DNA Barcode to Indonesia. Subsequently, the DNA sequence was registered into NCBI Genbank with the access code OR144414. This DNA barcode will be used as a standard for identifying A. molobrion and will aid in DNA and biotechnology-based studies in the future.